Older Workers' Perspectives in the Workplace and Challenges of Re-entering the Labor Market - Soseco, Thomas; Wijayanti, Febry; Prastiwi, Lustina Fajar; Dwiputri, Inayati Nuraini; Nurinda, Mei Sulfia; Markhamah, Siti; Qodri, Lutfi Asnan (Cita konsultindo, 2024)
This study investigates the perceptions of younger workers towards older workers in Srigonco Village, Malang Regency, Indonesia, amid a demographic shift characterised by a growing aging population. The research examines factors influencing older workers' re-entry into the labour market and the retirement preparedness of younger workers. Findings indicate a dual perception: while many younger workers value older employees for their experience and agricultural knowledge, they simultaneously express concerns about older workers' adaptability to new technologies and physical limitations. Specifically, 62.5% of respondents recognise that financial necessity drives many older workers to remain in the workforce, highlighting significant economic challenges. Moreover, 53.13% agree that older workers face discrimination and biases, which can hinder their employment opportunities. This research underscores the urgent need for inclusive labour market policies that accommodate the unique challenges faced by older workers while fostering collaboration between generations. Despite limitations in sample diversity and potential biases in self-reported data, the study emphasises the importance of intergenerational knowledge transfer for economic sustainability. Future research should adopt longitudinal and qualitative methods to gain deeper insights into the evolving dynamics between older and younger workers, focusing on effective policy interventions to improve employment outcomes for all age groups.